Mentoring and Tacit Knowledge Transfer in Novice Teachers From Chinese Middle Schools: Mediating Effect of Job Crafting - Xu, Jiying; Wei, Xueyan; Hisrich, Robert D.; Yu, Meifang; Li, Xue (Frontiers in Education, 2022)
In this study, we explore how the mentoring function relates to tacit knowledge transfer among Chinese novice middle school teachers as well as how job crafting mediates this relationship. In total, 465 Chinese novice teachers participated in the study completed a set of self-reports measuring the mentoring function, tacit knowledge transfer and job crafting. The analysis of the results indicated that: (1) The mentoring function, job crafting and tacit knowledge transfer were positively correlated;(2) Four sub-factors of the mentoring function were significantly related to tacit knowledge transfer, five sub-factors of job crafting were significantly related to tacit knowledge transfer; (3) job crafting played a mediating role between mentoring function and tacit knowledge transfer; (4) the mediating path of task crafting and skill crafting (two sub-factors of job crafting) between mentoring function and tacit knowledge transfer was significant, while the mediating effect of role crafting, cognitive crafting, and relationship crafting (the other three sub-factors of job crafting) was not significant.